2016
DOI: 10.4018/978-1-4666-9986-1.ch011
|View full text |Cite
|
Sign up to set email alerts
|

Video Games

Abstract: Until recently, research on video games has been concerned largely with negative effects of play. Increasingly, however, a range of positive psychological effects of playing video games are being reported. Being able to identify positive impacts is an important step toward leveraging the huge appeal of game playing to aid psychological well-being. This chapter discusses a range of benefits associated with playing two genres of popular off-the-shelf video games as opposed to video games that have been construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Emotional regulation and resilience appear to be key protective factors against the adverse outcomes of high-stress levels. It has been suggested that resilience and emotional regulation skills can be trained or promoted by the use of interactive media, including video games [37] , [43] , [44] . Therefore, this study investigated resilience and emotional regulation in the context of playing video games during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotional regulation and resilience appear to be key protective factors against the adverse outcomes of high-stress levels. It has been suggested that resilience and emotional regulation skills can be trained or promoted by the use of interactive media, including video games [37] , [43] , [44] . Therefore, this study investigated resilience and emotional regulation in the context of playing video games during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have argued that overcoming game obstacles to progress in a game and resolving game challenges share similarities with the skills needed in real life to cope with challenges and “bounce back” from stressful situations. Moreover, role playing with video game characters who overcome adversity can positively influence a player’s self-esteem [43] .…”
Section: Introductionmentioning
confidence: 99%